The Role of Quality Management System in Promoting Innovation in Companies - Marouane Saadia (Iraqi Journal of Science, 2021)
This article makes it possible to verify the role of quality management in strengthening the innovation process. The first hypothesis, according to which the quality (certification ISO 9001) influences the innovation positively, is confirmed for certain innovation indicators. Another hypothesis indicates that there are the levels of quality which develop the innovation process in diverse ways. The results indicate that for some domains of innovation, the performance of innovation of enterprises that have a very increased level of quality is higher than those of enterprises with an average quality, which in return is higher than those enterprises having a low quality level. Therefore, we discovered that the difference of performance innovation among enterprises having an average quality and those having a low level quality is not significant. This study suggests, thus, that in order to significantly ameliorate its innovation performance, the company must possess a quality system that is solidly established.